Kenya Food Security Simulator A Practical Demonstration and Announcement of a Blog Competition - CGIAR (2023)
The New Kenya Food Security Simulator: A Practical Demonstration and Announcement of a Blog Competition Co-organized by KIPPRA, University of Nairobi, IFPRI, and CGIAR Initiative on National Policies and Strategies (NPS) JULY 19, 2023 This video was recorded July 19, 2023 during the virtual workshop/seminar titled “The New Kenya Food Security Simulator: A Practical Demonstration and Announcement of a Blog Competition”